SUSTAINABLE MANAGEMENT STRATEGY FOR MANGROVE FOREST OF PELITA JAYA BAY AND KOTANIA BAY, WESTERN SERAM, INDONESIA - Tetelepta, Johannes M.S.; Loupatty, Sven; Wawo, Mintje (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2020)
The coastal area of Pelita Jaya Bay and Kotania Bay is a semi enclose estuary area having three typical most productive ecosystems i.e. mangrove, seagrasses, and coral reefs with the mangrove ecosystem being the dominant one making this area a productive in fish resources. Local community neighboring this area used mangrove ecosystem for many different purposes, some of it threatening the sustainability oh the ecosystem. The objective of this study was to analyze mangrove forest sustainability and to propose sustainable mangrove forest management. Rapfish analysis was used to analyze mangrove sustainability status. A sustainable management strategy was developed using a conceptual model framework combined with the DPSIR approach. The two most sensitive attributes affecting mangrove sustainability from Leverage analysis were used as the State component from DPSIR. The result shows that overall mangrove forest sustainability was 60% and was considered fair sustain with the ecological dimension having the highest sustainable scale (85.35%) and considered sustain, whilst institutional dimension having the lowest sustainable scale (29.10%) and considered unsustain. The sustainable mangrove management strategy proposed consists of workshops, training, vocational education concerning EAM, as well as replanting degraded mangrove forests, monitoring, surveying, and controlling. The management strategy should be conducted based on a co-management approach. Keywords: Mangrove forest, local community, sustainability, conceptual model framework, Kotania Bay